Doing good and/or avoiding bad: The ambidextrous view of managing corporate social activities - Xiong, Jie; Xu, Lu; Li, Qian; Yuan, Zhe; Chakraborty, Shubho (Management international / International Management / Gestiòn Internacional, 2023)
Our objective is to examine how firms manage corporate social activities across divergent orientations, either pro-CSR (corporate social responsibility) and/or anti-CSiR (corporate social irresponsibility) activities. We investigate two different approaches to managing corporate social activities, namely, balanced and combined, and study their potential impacts on corporate performance from an ambidextrous perspective. In addition, we examine the moderation effects of firm size and financial risk. We tested our hypothesis using a panel of 5,292 firms from KLD and COMPUSTAT between 1998 and 2015.